As ouvidorias de saúde pública no Estado do Pará: uma relação dialógica entre governo, medicina e sociedade? - MORAES, Diana Coeli Paes de (Universidade Federal do Pará, 2014)
That paper emphasizes about the Public Health's Offices as an area of citizen participation in administrative management inquiring if it happens a Dialogic Dynamics Relationship between Government, Medicine and Society in the perspective of harmonization of management and services provided by public health in accordance with the policy of Humanization by SUS. The guiding hypothesis of the study it is the popular participation trough’s offices are produced transformations in practice played by different actors in setting health care practices in alignment with the principles and strategies humanization of the single health system with ability of tension arising in the biomedical context roles that became as prevalent from on 17th century. The point of view is to identify the effective contributions of the performance of public health's offices in building and implementing new practices of health according to the PNH. It was be developed in four chapters, dealing with social participation and the history of public health's offices in Brazil, the SUS and the Humanization of Health Policy, research itself and conclusion. The qualitative and exploratory design research that seeks to know, describe and understand the reality of the policy of humanizing public health institutions in the State of Pará, through the demands of offices in a process of expansion of democratic mechanisms of social control of public health policies. Among the results achieved in this research what it's discussed, it is that the public health's offices has the clear commitment to become an institution of excellence and fulfill its role in promoting dialogue between the State, Medicine and Society. As for this process to collaborate in the construction of new practices in health, it doesn’t identify effectiveness. However, as symbolic value of representativeness, accessibility, communication and dialogue without bureaucracy between Society and the Public Administration it is significant. It’s noted how important that was the Public Health Management to organize in their multiple instances.